Assessing First-year Physician Assistant Students about Physical Activity - Conroy, Jillian (My University, 2025)
Introduction. Even though physical activity has proven to be extremely beneficial in several healthcare aspects, it is not commonly prescribed. One cause of this is a lack of physical activity curricula in healthcare professional education. The purpose of this study was to examine the knowledge, attitudes, and skills of first-year Physician Assistant students about personal physical activity as well as perceptions of prescriptive physical activity. Methods. Within the Fall 2024 semester, two physical activity-based lectures were given to first-year ECU Physician Assistant students. Each participant completed a Qualtrics questionnaire twice. Once in August before listening to the lectures and once in November after listening to the lectures. The questionnaire contained several sections such as demographics, personal physical activity history, current physical activity history, and perceptions of prescriptive physical activity. Within the questionnaire, post-lecture improvement was looked for in the following three research categories: overall physical activity knowledge, knowledge of physical activity benefits, and confidence to prescribe physical activity. Results. While comparing pre- and post-lecture data in a paired samples T-Test, it was concluded that participants (N = 24; 91.7% female, 75% White) showed no improvement in any of the research categories. In the first research category, overall physical activity knowledge, the pre-lecture and post-lecture were similar as the P-value (P = 0.258) showed no statistical significance. For research category, knowledge of physical activity benefits, participants showed more improvement than category one, but not enough to be statistically significant (P = 0.081). In the third research category, confidence in physical activity prescription, participants showed the most practical improvement, but it was not enough to be considered statistically significant (P = 0.063). Conclusion. Findings demonstrate that a series of two physical activity lectures did not improve students’ physical activity knowledge or confidence to prescribe physical activity. However, these findings suggest that including physical activity education in a healthcare curriculum could be a step in making exercise prescription more popular in the United States.
Keywords: Physical Activity